Inheritance of dwarfism in AAB plantains - Ortíz, R.; Vuylsteke, D.R. (Wiley, 1995)
Plantain (Musa spp., AAB group) is a major food crop in the humid lowland tropics of Africa, the Caribbean and Latin America. Lodging, caused by strong winds occurs periodically in these areas. Therefore, development of dwarf plantain cultivars and elucidation of the inheritance of dwarfism is desirable. A heterozygous normal plantain cultivar (2n= 2x) with long false‐internodes (19.4 ± 0.9 cm) was crossed with a homozygous wild banana (2n= 2x) with short false‐internodes (6.9 ± 0.4 cm) to develop a test‐cross segregating population. A total of 74 euploids (2x, 3x and 4x) were produced. Forty‐one normal and 24 dwarf diploids were obtained, which fits a 2: 1 trisomic test‐cross segregation ratio for one locus. Dwarfism is controlled by a single recessive gene, dw. At the tetraploid level, two normal and six dwarf hybrids were produced, suggesting that the dw locus is close to the centromere and that there is a dosage effect of the dw allele at the tetraploid level.